Sustainable microgreen production through automated cultivation systems: nutritional and functional profiling via multivariate analysis - Taşcı Durgut, Figen; Eryılmaz Açıkgöz, Funda; Özdüven, Fatma Funda; Yıkmış, Seydi (Frontiers in Sustainable Food Systems, 2025)
This study aimed to evaluate the performance of a fully automated microsprout production cabinet system developed with a sustainable food processing perspective and to compare the nutritional and functional properties of microsprouts produced in different growing environments. Leek, amaranth, and purslane microsprouts were grown in fully automated (confetti cabinet) and standard laboratory environments. Microsprout samples were analyzed for dry matter, protein, vitamin C, macro- and microelement contents, and total antioxidant capacity. According to the results, leek samples grown in the cabinet showed significantly higher vitamin C content than those grown in the laboratory environment (74.27 ppm vs. 62.68 ppm, p < 0.05). The highest antioxidant capacity was detected in purslane samples, with an EC50 value of 174.64 μg/mL. Furthermore, the nitrogen content was measured at high levels in all species, ranging from 6.14 to 7.62%. PCA and correlation analyses revealed significant differences in the distribution of certain micronutrients (e.g., Na, Mg, B) across different production environments. These findings demonstrate that fully automated production cabinets provide effective, sustainable, and traceable systems for producing micro sprouts with high nutritional quality, and have significant potential for future applications in functional food production.